A Development of Android-based Mobile Application for Getting Ideal Weight - Alvina Aulia; Fidelson Tanzil; Irma Kartika Wairooy; Leonardus Kristian Gunawan; Alvin Cunwinata; Albert Albert (Universitas Ahmad Dahlan, 2018)
The development of this application has a goal to give people who don’t have any idea of how to keep an ideal body weight and to maintain it by having controlled food intakes and exercises. This application is designed by using a Waterfall Model, a 5-phase model that is Communication, Planning, Modeling, Construction, and Deployment starting from as the aforementioned steps. Based on the responds we get from distributing questionnaire, many people didn’t know how to exercise properly and didn’t bother to check the calories of their food. Their weight is also a problem because most of them still have an Overweight or Underweight status. From those responds, we can conclude that our application will indeed help people to get and maintain their ideal body weight.